PREDICTIVE POWER OF THE INTRAOPERATIVE EVALUATION OF RETROAREOLAR MARGIN IN MAMMARY ADENECTOMIES FOR THE TREATMENT OF EARLY-STAGE BREAST CANCER - Heinzen, Rebeca Neves; Barros, Alfredo Carlos Simões Dornellas de; Carvalho, Filomena Marino; Aguiar, Fernando Nalesso; Jacomo, Alfredo Luiz (Mastology, 2020)
Introduction: Mammary adenectomy (MA) has been increasingly adopted to treat early-stage breast cancer (BC) for its cosmetic benefits and oncologic safety. In order to ensure the local control of the disease, the amount of remaining glan-dular tissue should be the least possible, and surgical margins must be free. Objective: To evaluate the predictive power of the intraoperative evaluation of retroareolar margin (IERM) compared to the gold-standard represented by the definitive analysis of sections embedded in paraffin. Method: This is a retrospective cohort study conducted with patients from the Clínica Professor Alfredo Barros, based on 224 individuals submitted to surgery with the MA technique (178 infiltrating carcinomas and 46 ductal carcinomas in situ). In all patients, the distance tumor-nipple-areola complex (NAC) was ≥2.0 cm, according to magnetic resonance imaging (MRI). A 0.5 cm thick flap was used in the region below the NAC. IERM was performed through cytopathological and histopathological examinations. IERM findings were compared to those of the definitive paraffin examination to calculate the parameters of predictive power. Results: In 5 cases (2.2%), IERM was positive, and NAC was immediately removed. The parameters of IERM predictive power can be seen below: Sensitivity 100%, Specificity 100%, Positive predictive value 100%, Positive negative value 97,3%, Accuracy 98,2%. Conclusion: IERM is highly accurate, has full specificity, and the NAC can be managed intraoperatively according to its result.